Responses of leaf functional traits to different hydrological regimes and leaf economics spectrum in the water level fluctuation zone of Three Gorges Reservoir, China - Li, Xiaoling; He, Di; Chen, Gong; Yang, Jin; Yang, Zhengjian; Guo, Xiao juan; Wang, Congfeng; Zhu, Shijiang; Huang, Yingping; Chen, Hongfeng; Huang, Guiyun; Zhang, Dingjun; et al. (Frontiers in Plant Science, 2022)
A unique riparian ecosystem has been created as a result of anti-seasonal flooding after reservoir operations, which notably influence distribution patterns of plant communities and functional characteristics in riparian zone. Plant functional traits which reflect the physiological and ecological processes of plants in particular ecosystems are crucial for indicating the variations of ecosystem structure and function. To better understand the adaptation strategies of plants to hydrological changes, and provide scientific basis for the selection of species in the re-vegetation of the newly-formed ecosystems, the 14 leaf functional traits and leaf economics spectrum (LES) of the 19 dominant plants under different hydrological conditions were investigated in the water level fluctuation zone (WLFZ) of the Three Gorges Reservoir (TGR). The results showed that anti-seasonal flooding has significant effects on the leaf functional traits of plants (P<0.05). The net photosynthetic rate of annual plants was significantly higher than that of perennial plants (P<0.05), and there was a significant correlation between leaf phenotypic traits and leaf photosynthetic traits (P<0.05). Canonical correspondence analysis showed that soil water content and available phosphorus were the main factors affecting leaf function of dominant species, indicating that hydrologic factors were still important environmental factors affecting leaf functional traits of dominant species in the WLFZ. And annuals from the WLFZ have characteristics of thick leaves, high photosynthetic rate, short lifespan, and high nutrient concentrations, which make them close to the fast investment-return of LES. On the contrary, perennials are close the slow investment-return end of LES. The high productivity investment of annuals is better than the high defense investment of perennials for adapting the special habitats in the WLFZ. These results indicated that different functional plants in the WLFZ of the TGR under different hydrological regimes can adopt different strategies by weighing the associations and trade-offs between their economic traits.